2009
DOI: 10.1007/s00384-009-0794-z
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine is effective for short-term treatment of slow transit constipation: a double-blind placebo-controlled clinical trial

Abstract: This trial shows that low-dose colchicine is effective in treatment of slow transit constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…The mechanism of inducing diarrhea by colchicine is unknown. It has been reported that colchicine increases prostaglandin synthesis, intestinal secretion and gastrointestrial motility 45. It also reduces water and electrolyte absorption in the intestine and increases secretion through a cyclic AMP mediated activity.…”
Section: Prevention and Management Of Constipation In The Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of inducing diarrhea by colchicine is unknown. It has been reported that colchicine increases prostaglandin synthesis, intestinal secretion and gastrointestrial motility 45. It also reduces water and electrolyte absorption in the intestine and increases secretion through a cyclic AMP mediated activity.…”
Section: Prevention and Management Of Constipation In The Elderlymentioning
confidence: 99%
“…In a double-blind, placebo-controlled study of patients with STC (n = 60), colchicine was shown to be effective in lowering Knowles-Eccersly-Scot symptoms (KESS) scores 45. KESS is a valid technique in diagnosing and evaluating symptoms of constipation.…”
Section: Prevention and Management Of Constipation In The Elderlymentioning
confidence: 99%
“…The duration of constipation prior to inclusion ranged from 6 months to at least 1 year . Other studies used the Rome II or Rome III criteria for functional constipation, implying minimum duration of 12 and 6 months, respectively. Still, other studies used terms like “several years” .…”
Section: Resultsmentioning
confidence: 99%
“…In an 8-week controlled trial in patients with slow transit constipation, colchicine 1 mg daily was superior to placebo in improving a combined constipation symptom severity score [56].…”
Section: Other Agentsmentioning
confidence: 99%